Analytical Methods of Predicting the Structure and Mechanical Properties of High Tensile Strength Steel. (2017) - Piekarska, Wiesława; Goszczyńska-Króliszewska, Dorota
Abstract: The analytical methods of the analysis of phase transformations as well as predicting the structure of welded elements are presented in the paper. The characteristic values, such as the temperatures of the start and finish of phase transformations are determined by taking into account the empirical relations. Furthermore, the start and finish temperatures of phase transformations corresponding to cooling rates v 8/5 ( t 8/5 ) are defined. On the basis of the designated values, the computational welding CCT diagrams of S355 steel are prepared. Analytically obtained CCT diagram is compared with results obtained by dilatometric research. The prediction of mechanical properties of steel is presented on the basis of analytical relationships. On the basis of structural composition of S355 steel and analytical relationships are obtained mechanical properties such as hardness ( HV ), yield strength ( R e ), tensile strength ( R m ), elongation ( A ) and the contraction ( Z ). Experimental studies of steel are performed in order to verify obtained results.